2020
DOI: 10.3390/met10040509
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of the Static and Dynamic Behaviour in a Quenching and Partitioning Processed Low-Si Steel

Abstract: Because of their excellent combination of strength and ductility, quenching and partitioning (Q & P) steels have a great chance of being added to the third generation of advanced high strength steels. The large ductility of Q & P steels arises from the presence of 10% to 15% of retained austenite which postpones necking due to the transformation induced plasticity (TRIP) effect. Moreover, Q & P steels show promising forming properties with favourable Lankford coefficients, while their planar anisotropy is low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…1.27b. The suppression of TRIP effect due to increased strain rate was also reported in [197], where the RA transformation was retarded when the strain rate reached to 500 s −1 . However, such effect of strain rate on RA transformation was not observed in Q&P 980 steel studied by interrupted SHTB tests [198].…”
Section: High Strain Rate Tensile Behaviorsupporting
confidence: 61%
“…1.27b. The suppression of TRIP effect due to increased strain rate was also reported in [197], where the RA transformation was retarded when the strain rate reached to 500 s −1 . However, such effect of strain rate on RA transformation was not observed in Q&P 980 steel studied by interrupted SHTB tests [198].…”
Section: High Strain Rate Tensile Behaviorsupporting
confidence: 61%
“…Vercruysse et al [8] studied the static and dynamic tensile properties of a Q&Ptreated Fe-0-2C-1.25Si-2.4Mn-0.023Al (wt.%) steel in the temperature range from −40 • C to 80 • C. The material showed excellent low-temperature tensile properties because of the high thermal stability of retained austenite, which could contribute to the transformationinduced plasticity (TRIP) effect during testing at low temperatures. However, uniform elongation significantly dropped at 80 • C due to less effective use of the TRIP effect at this temperature.…”
Section: Contributionsmentioning
confidence: 99%
“…Although some research has been carried out on the effect of the stability of austenite on hydrogen susceptibility, it is still not completely understood. In earlier publications of the authors, it was reported that imposing a high strain rate, as would be the case in a car crash, affects the TRIP effect due to the adiabatic heating influencing the stability of austenite [4]. Therefore, the present research is focused on the effect of the addition of Nb on the HE susceptibility of a Q&P steel under static and dynamic loading conditions.…”
Section: Introductionmentioning
confidence: 97%